2018
DOI: 10.1016/j.bcmd.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker signatures of sickle cell disease severity

Abstract: Identifying sickle cell disease patients at high risk of complications could lead to personalized treatment and better prognosis but despite many advances prediction of the clinical course of these patients remains elusive. We propose a system-type approach to discover profiles of multiple, common biomarkers that correlate with morbidity and mortality in sickle cell disease. We used cluster analysis to discover 17 signatures of 17 common circulating biomarkers in 2320 participants of the Cooperative Study of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
1
20
0
1
Order By: Relevance
“…Our findings are in agreement with the pathophysiological mechanism of VO due to i) heightened ability of sickle RBC to adhere to the vascular endothelium and promote activation of endothelial cells and leukocytes and ii) sickle RBC have the lifespan shortened which also contributes to anemia [42]. Cluster grouping is a very useful approach to identify biomarkers of SCD severity [43]. We designed a cluster analysis in order to group the laboratory parameters of each genotype.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are in agreement with the pathophysiological mechanism of VO due to i) heightened ability of sickle RBC to adhere to the vascular endothelium and promote activation of endothelial cells and leukocytes and ii) sickle RBC have the lifespan shortened which also contributes to anemia [42]. Cluster grouping is a very useful approach to identify biomarkers of SCD severity [43]. We designed a cluster analysis in order to group the laboratory parameters of each genotype.…”
Section: Discussionsupporting
confidence: 83%
“…Another study of the same cohort reported a higher baseline hematocrit was associated with 1 or more painful crises [ 22 ]. However, a detailed study of biomarker clusters in this cohort found patients with less intravascular hemolysis had a reduction in pain and acute chest syndrome in addition to a trend to reduced mortality and stroke [ 23 ]. High hemoglobin F levels have also been associated with reduced incidence of acute painful episodes [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…This group has also published analysis of laboratory measurements of carbon monoxide and heme oxygenase for acute pain crisis prediction [41]. Other groups have studied red blood cell mechanical sensitivity and biomarker signatures of SCD severity [42,43]. The use of machine learning in a variety of areas of medicine including outcome prediction for chemoradiotherapy, breast cancer survival prediction, and early prediction of asthma exacerbations have recently been published [44-46].…”
Section: Discussionmentioning
confidence: 99%